Maternal self-efficacy and 1–5-year-old children’s brushing habits - Finlayson TL, Siefert K, Ismail AI, Sohn W. (Blackwell Synergy, 2007)
This study investigates the relationships between maternal cognitive, behavioral, and psychosocial factors and brushing practices in low-income African-American preschool children.